Determination of tsetse challenge and its relationship with trypanosome prevalence in livestock within the African Trypanotolerant Livestock Network - Leak, S.G.A.; Awuome, K.; Duffera, W.; Dumont, P.; Feron, A.; Jeannin, P.; Mahamat, B.; Mawuena, K.; Minengu, M.; Mulungo, M.; Nankodaba, G.; Ordner, G.; et al. (OAU/STRC, 1988)
Determines the tsetse challenge and its relationship with trypanosome prevalence in livestock at eleven sites within the African Trypanotolerant Livestock Network. Includes tsetse species, their distribution, habitats, and relative density; trypanosome infection rate; and frequency of vivax and congolense - type infection; also shows the overall tsetse challenge determined from the product of relative density; and tsetse challenge and trypanosome prevalence for trypanotolerant and other cattle herds.